The Actualisation of Regional Capacity Educational Space Based on Cluster Interaction: The Aspect of Formation of Training Health Culture - V. A. Fedorov; K. V. Chedov (Образование и наука)
Introduction. Secondary schools are the only social institution through which the entire child population passes. This suggests that the general education system is the most important link in the socialisation of an individual, where a health culture is formed among other values. Currently, in Russian and foreign pedagogical science and practice, there are various models for organisation of the activities of educational institutions in the formation of a health culture of students. However, individual institutions often require more strength and capacity to achieve the desired outcome.The aim of the research is to substantiate the theoretical and methodological foundations of the integration of resources and capabilities of various social institutions in the context of their cluster interaction within the regional educational space in order to form a culture of students’ health.Methodology and research methods. In the course of the research, the multilevel concept of methodological knowledge is used. At the philosophical level, the axiological approach, which is of particular importance in the conditions of protecting the health of the younger generation, is taken as a fundamental one, since health is a universal (highest) human value and the main value orientation of the personality (A. Maslow), which determines the healthy and full development of the individual. The general scientific level is represented by a system-interactionist approach, which is a correlation of systemacity and interaction. The system component of the approach involves the consideration of the object (organisation, pedagogical system, educational space, etc.) not as a simple sum of any separate components, but as a single functional whole that has its own qualities distinguishable from the qualities of its individual parts. The interactionist component of the approach involves solving a pedagogical problem through the influence, communication, transition, development of various objects under the influence of mutual actions on each other, on other objects. The specific scientific level includes an integrative approach, involving the implementation of the educational process in educational organisations based on the use of resources of all members of educational activity. The technological level allows for phased planning, sequentially solving tasks and interpreting the results. The administrative and managerial aspect of the technological level is represented by a cluster approach, and the psychological and pedagogical one is represented by a personal-activity one. To achieve this goal, the following generally accepted research methods were used: conceptual-terminological and theoretical-methodological analysis, comparison, interpretation, theoretical modeling, generalisation, formative pedagogical experiment.Results and scientific novelty. The concepts of “regional educational space” and “cluster on the formation of a health culture of students in the regional educational space” were defined. Theoretical and methodological foundations for the integration of resources and capabilities of various social institutions in the context of their cluster interaction within the regional educational space with the aim of creating a health culture for students have been developed and described. Structural functional model and process flow chart of such interaction have been constructed.Practical significance. The results of the research create the prerequisites for a systematisation of the activities of specialists in the field of education, other social institutions and local executive authorities in the creation and development of regional clusters in the interests of protecting the health of the younger generation.